Zur Geschichte der Psychotherapie in der DDR - Maaz, Hans-Joachim (European Journal of Mental Health, 2011)
Some Remarks on the History of Psychotherapy in the GDR: The article presents the history of psychotherapy in the GDR giving special attention to the development of psychodynamic and psychoanalytic methods. The battle around psychoanalytic theory and practice was not only significant from the aspect of therapeutic conceptions but also with regard to the personal development of psychotherapists and in view of the fact that it provided an opportunity to keep distance from the politics and ideology of the GDR. The study gives an overview of the wide range of psychotherapeutic methods applied in the GDR. The remarkable development of psychotherapy in the GDR is aptly shown by the organisational structure of psychotherapy in that country; this structure was set up by the Society for Medical Psychotherapy of the GDR, the Psychological Society of the GDR and the regional associations. Another indicator for the development can be seen in the way neurotic-functional disorders were diagnosed and treated in a mutually supportive system involving psychotherapy specialists, medical psychologists and specialised psychotherapy. The study also describes the difficulties involved in the social recognition of GDR psychotherapy up to the times of the political turn in the country, when psychotherapy practiced in the GDR merged into the guideline-based psychotherapeutic system prevailing in the Federal Republic of Germany. The article pays tribute to the work carried out by influential psychotherapists in the GDR.